How graduate students seek for information: Convenience or guaranteed result? - S., Liyana; A., Noorhidawati; Liyana, S.; Noorhidawati, A. (Malaysian Journal of Library and Information Science, 2017)
Liyana, S., & Noorhidawati, A. (2014). How graduate students seek for information: Convenience or guaranteed result?. Malaysian Journal of Library & Information Science, Vol.19, no. 2: 1-15. This paper reports on the information seeking behaviour of computer science graduate students. The following research questions are put forward to address the main research objective on how graduate students seek for information: i) what type of information resource do computer science graduate students use?; ii) how do computer science graduate students seek and obtain information?; iii) what are the problems faced by computer science graduate students while seeking information?; iv) does any relationship exist between the use of different information resources and graduates’ demographic information (i.e., age and type of graduate program)?; v) does any relationship exist between the use of different information resources and problems in finding information?and vi) does any relationship exist between the use of different information resources and success in finding information?. A survey was conducted at the Faculty of Computer Science and Information Technology, at the University of Malaya, with a sample size of 217 graduate students. The data gathered was analysed quantitatively using SPSS statistical software. The findings show that even though the Internet Search Engine is the first information resource used by computer science graduate, they are however still in doubt with the trustworthiness of the information they retrieved. This has made the students dissatisfied with their initial findings that led them to use more reliable information resources, such as digital libraries and online databases. This study provides insights into how computer science graduate students seek information that offers improvement implications to the development of available information resources and library services.